Competitive Debate as Innovation in Gamification and Training for Adult Learners: A Conceptual Analysis - Sánchez Prieto, Guillermo A.; Martín Rodrigo, María José; Rua Vieites, Antonio (Frontiers in Psychology, 2021)
Adult learners demand teaching innovations that are ever more rapid and attractive. As a response to these demands and the challenges of skills training, this article presents a conceptual analysis that introduces competitive debate as an impact training model. The aim is to learn whether debate can be considered to fall within the frame of gamification, so that the full potential of debate as gamification can be exploited. There is a significant research gap regarding competitive debate as a game, with the training mechanics for adult learners remaining practically unexplored. Through a conceptual analysis of game, game experience, and gamification, and their respective characteristics, we conclude that competitive debate is an ideal instrument for gamification.